Mechanical Response of PbSSe, PbSTe Ternary and PbSnSTe Quaternary Alloys at High Pressure - Othman, Mazin Sh. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
Property of the semiconductors under high pressure is investigated by the density functional theory and paralleled to the foretelling of the linear elasticity theory. In addition, ternary alloys of PbSxSe1-x and PbSxTe1-x lattice matching PbS substrate for x = 0.5 compositions are studied. Furthermore, quaternary alloys PbxSn1-xSyTe1-y lattice matching PbS substrate for x and y = 0.5 compositions are studied. The six independent elastic parameters (Cij) are also calculated. Meanwhile, the results data are analyzed in high pressure. The mechanical response of all alloys to pressures 0, 50, and 100 kbar increases progress to decrease in (Cij) in separate rates. The rapprochement between the calculated results and the available published data for these alloys demonstrate that they had worthy accordance at zero pressure and the results at high pressure may be required as an acceptable reference.